Fish physiology and ecology: the contribution of the Leigh Laboratory to the collision of paradigms - NW Pankhurst; NA Herbert (New Zealand Journal of Marine and Freshwater Research, 2013)
The often pragmatic division of studies of function (physiology), and the regulation of distribution and abundance of organisms (ecology), as laboratory and field studies respectively, can create an unhelpful intellectual division that runs the risk of ignoring the interaction of physiology, behaviour and environment that regulates the lives of animals in the wild. This review examines the historical and current contribution of ecophysiological research conducted from the University of Auckland's Leigh Laboratory in bridging these paradigms, and generating new insights into animal function and community organisation. The assessment focuses on endocrine control processes, and metabolic and behavioural responses of fish to artificial and natural stressors, and examines tracks of future research needed to underpin understanding of likely effects of predicted environmental change on individuals and populations.